2020
DOI: 10.1159/000506327
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of a Patient with anti-PD1 Antibody-Resistant Advanced Mucosal Melanoma with Nivolumab, Ipilimumab plus Denosumab Combination Therapy

Abstract: Since the incidence of mucosal melanoma is higher in the Japanese population compared to Caucasians, and since mucosal melanoma possesses a lower mutation burden compared to cutaneous melanoma, the efficacy of anti-PD1 antibody (Ab) monotherapy for mucosal melanoma is limited. Therefore, other targeting molecules that enhance the anti-tumor effects of immune checkpoint inhibitors are needed. In this report, we present a case with anti-PD1 Abresistant recurrent malignant melanoma of the nasal cavity successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In this case, the patient was offered this cocktail of immunotherapy; however, her pregnancy complicated matters. There have been a few case reports in which nivolumab or ipilimumab with denosumab have been shown to be effective in the treatment of mucosal melanomas [ 13 , 14 ]. Such immunotherapy has been classified as pregnancy category D by the Food and Drug Administration, which means that the drugs in this class may be used in pregnancy if the benefits to the mother outweigh the risk to the fetus [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the patient was offered this cocktail of immunotherapy; however, her pregnancy complicated matters. There have been a few case reports in which nivolumab or ipilimumab with denosumab have been shown to be effective in the treatment of mucosal melanomas [ 13 , 14 ]. Such immunotherapy has been classified as pregnancy category D by the Food and Drug Administration, which means that the drugs in this class may be used in pregnancy if the benefits to the mother outweigh the risk to the fetus [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few case reports in which nivolumab or ipilimumab with denosumab have been shown to be effective in the treatment of mucosal melanomas [ 13 , 14 ]. Such immunotherapy has been classified as pregnancy category D by the Food and Drug Administration, which means that the drugs in this class may be used in pregnancy if the benefits to the mother outweigh the risk to the fetus [ 13 , 14 ]. As a result, immune checkpoint inhibitors are discouraged during pregnancy, as one case series showed that 88.9% of pregnant patients on immunotherapy had premature onset of labor, while 71.4% had other complications such as intrauterine growth restriction, placental insufficiency, and lower fetal heart rates [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although most melanoma tumors develop in the skin (cutaneous melanoma), they can also arise in mucosal membranes, [10][11][12][13][14][15][16][17], in the eye (uveal melanoma) [18], and primary melanoma tumors have also been described in leptomeninges (Table 1) [19]. Among these different types of melanoma, cutaneous melanoma is by far the most prevalent.…”
Section: Cutaneous and Non-cutaneous Melanomamentioning
confidence: 99%
“…As yet, the available evidence for ICI is based on single case reports, retrospective analyses and small study subpopulations in clinical trials. In two published cases of metastatic mucosal melanoma, a complete remission was seen following Nivolumab, Ipilimumab plus Denosumab combination therapy [ 19 ] and Nivolumab monotherapy [ 20 ], respectively. In a pooled analysis from six prospective clinical trials, the data of 157 patients with unresectable or metastatic mucosal melanoma were analyzed.…”
Section: Introductionmentioning
confidence: 99%